Estudio de la capacidad de adsorción de plomo por la biomasa de semillas de Caesalpinia spinosa en soluciones acuosas - Soto Lozada, Junior Paul (2017)
The investigation was developed in laboratory’s conditions with the purpose of determine the adsorption’s capacity of the biomass in the seeds of Caelsapinia spinosa against solutions contaminated with lead, determining the dosing curves keeping the agitation at 400 rpm for a period of 24 hours at environment temperature, was used a design an experimental with factorial model, the samples were analyzed by atomic absorption; obtaining in the saturation point with lead with biomass of 0,7; 0,8 and 0,9 grams with a maximum removal capacity of 96%. The experimental data was evaluated applying the kinetic models of pseudo-first order and pseudo-second order, as result the data was adjusted to the pseudo-second order model; in addition, the kinetic parameters and the lead elimination time were evaluated, the data were analyzed with the analysis of variance test and for the cases in which significant differences were evidenced with the Minimum Significant Difference Honest methodology, for treatments and times of exposure; with which it was arrived at the conclusions that the biomass in the seeds of Caelsapinia spinosa presents capacity of adsorption of lead and reached the equilibrium by saturation of lead in the absorbent.